(untitled) (Eurasian Medical Research Periodical, 2024)
The article is devoted to the study of the diet of schoolchildren and their health. Nutrition is one of the main factors that determine not only the quality of life, but also the conditions for a child’s development. It is known that any deficiency, especially protein and vitamin deficiency, can slow down growth processes and worsen the psychophysiological state of the developing organism